(untitled) (Research, Society and Development, 2022)
Much research has been carried out to investigate strategies that aim to overcome students’ difficulties in learning algorithms and programming. One of the approaches used as an alternative to traditional methods is Gamification, which is the use of game elements in non-game-focused contexts, with the intention of engaging people, promoting learning and solving problems. In view of the possibilities that may arise from the use of game elements in educational environments, this article aims to investigate the gamification strategy in the context of teaching programming, as well as reviewing how this strategy has been applied in this scenario through a tertiary study that analyzed Systematic Reviews of Literature that researched on this topic. The analyzed questions sought to answer which gamification elements are being addressed in programming teaching; which programming contents are being gamified; and what are the benefits and limitations of current research. For this, a tertiary review was carried out that analyzed four articles from Systematic Reviews of Literature on this theme, with the articles being analyzed and qualified individually. As a result, it was identified that despite the many researches that have been carried out using gamification strategies in programming teaching have shown positive results, there is still a need to pay attention to the creation of gamified solutions that better combine gamification elements in order to produce a truly meaningful learning experience.